2011
DOI: 10.1590/s0102-33062011000100008
|View full text |Cite
|
Sign up to set email alerts
|

Produção de serapilheira e ciclagem de nutrientes de um reflorestamento e de uma floresta estacional semidecidual no sul do Brasil

Abstract: ABSTRACT(Litter production and nutrient cycling in a reforested area and a seasonal semideciduous forest in southern Brazil). Th e aim of this study was to evaluate litter production, N, P, K, Ca and Mg content, nutrient transfer, and litter decomposition rate of a seasonal semideciduous forest and an adjacent reforested area. Th e study was carried out in Godoy Forest State Park (GFST), Paraná state, Brazil. Estimated annual litter production was 8,212 kg.ha -1 .year -1 in the forest and 5,341 kg.ha -1 .year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 12 publications
4
14
2
17
Order By: Relevance
“…2A, mean monthly litter production was significantly higher in September than in June, December, January, April, and May (F=3.11; p<0.05). Similar results were obtained by Vital et al (2004) and Pimenta et al (2011). August and September were also the months with the highest leaf production (33.49 kg.ha −1 .…”
Section: Litter Productionsupporting
confidence: 85%
See 2 more Smart Citations
“…2A, mean monthly litter production was significantly higher in September than in June, December, January, April, and May (F=3.11; p<0.05). Similar results were obtained by Vital et al (2004) and Pimenta et al (2011). August and September were also the months with the highest leaf production (33.49 kg.ha −1 .…”
Section: Litter Productionsupporting
confidence: 85%
“…The lower density and basal area of species in the EF (Gris 2011) is related to the lower annual litter production in early successional forest (Pinto et al, 2009). The annual litter production of the RLF evaluated in the present study was higher than that reported in studies conducted in other reforested areas of SDFs in southern Brazil, including the 5341 kg.ha −1 reported by Pimenta et al (2011) and the 6636 kg.ha −1 reported by Moreira & Silva (2004). That difference might be due to the fact that, in the RLF studied here, the proportions of deciduous or semideciduous species and exotic species are higher than expected for a typical SDF (Gris 2011;IBGE 2012).…”
Section: Litter Productioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Pimenta et al (2011) relacionaram a menor decomposição no reflorestamento à maior luminosidade e à menor umidade relativa, devido à maior abertura do dossel. Kolm e Poggiani (2003), ao estimar a taxa de decomposição da serapilheira em plantações de Eucalyptus grandis com 20 anos, em diferentes intensidades de desbaste, com 0%, 67% e 83%, encontraram respectivamente 0,56, 0,81 e 0,70 para os valores da constante de decomposição (K).…”
Section: Taxa De Decomposição Da Serapilheiraunclassified
“…É o remanescente com vegetação arbórea mais rica do município, possuindo 134 espécies (Kotchetkoff-Henriques, 2003). Pelo seu tamanho e pela sua localização entre a zona urbana e monocultura de cana de açúcar, este fragmento sofre forte impacto do entorno e está em estádio secundário de desenvolvimento, apresentando alterações na estratificação da vegetação, com aberturas no dossel em muitos pontos (Souza, 2005;Camargo, 2008) e com bordas e clareiras infestadas por lianas (Bonatti, 2007 (König et al, 2002;Pimenta et al, 2011;Pinto et al, 2009 Também diminui a velocidade da água que corre sobre o solo durante a chuva, amenizando a perda de nutrientes (Poggiani, 1989).…”
Section: Floresta Referência: a Estação Ecológica De Ribeirão Pretounclassified